Estimating leaf area of basil cultivars through linear dimensions of leaves - da Silva Ribeiro, João Everthon; Silva Nóbrega, Jackson; dos Santos Coêlho, Ester; Jardelino Dias, Thiago; Ferreira Melo, Marlenildo (Revista Ceres, 2022)
Ocimum basilicum L. (basil) is an annual herb belonging to the Lamiaceae family that has economic importance for many regions around the world. Thus, ecophysiological studies are needed to assess this species growth and dispersal. This work aimed to obtain equations from regression models that meaningfully estimate the leaf area of basil cultivars using linear dimensions of leaves. For this purpose, 300 leaves from ‘Italiano Roxo’ and 500 leaves from ‘Folha Fina’ cultivar were collected from plants cultivated in a greenhouse. Then, the length, width, and leaf area of each leaf were measured, and product of length by width were calculated. The equations were adjusted using the simple linear, linear without intercept, quadratic, cubic, power, and exponential regression models. Criteria for selecting the best equations were highest determination coefficient and Willmott’s agreement index, lowest Akaike information criterion and root mean square error, and BIAS index closest to zero. All the equations fitted using the product of length by width (L.W) can estimate the leaf area of basil cultivars. Thus, basil leaf area can be estimated through a non-destructive method using linear dimensions of leaves. However, the equation w = 0.8175*LW0.9307 is the most suitable for ‘Italiano Roxo’ and w = 0.6335*LW for ‘Folha Fina’.